Application of the Jigsaw Model to the Human Excretory System Material as an Effort to Improve Student Learning Activities - Nafis, Badratun; Zahara, Nurlia (Indonesian Journal of Education and Social Humanities, 2024)
The use of less varied learning models is one of the factors that can affect student activity in the learning process, which can lead to low student learning outcomes. One of the steps taken to overcome this problem is to apply the jigsaw cooperative learning model. This study aims to evaluate student learning activities taught through the application of the jigsaw cooperative learning model on the human excretory system material. The results of data analysis on student learning activities at the first meeting showed an average percentage value of 75.37%, which is included in the active criteria. At the second meeting, the average percentage value of student learning activities increased to 84.7%, which is included in the very active criteria. From these data, it can be concluded that the application of the jigsaw cooperative learning model has a positive effect on increasing student learning activities on the human excretory system material at State Junior High School 3 Indrapuri.